Impulsivity in multiple sclerosis: A paired case-control study - Tutuncu, Mesude; Acar, Zeynep; Koseoglu, Mesrure; Sariahmetoglu, Hande; Gozubatik Celik, Gokcen; Burcu Dogan, Vasfiye; Soysal, Aysun (Annals of Medical Research, 2021)
Aim: The presence of neuropsychiatric disorders in patients with multiple sclerosis (MS) has been recognized since Charcot first described the disease and reported at rates reaching 60%. However, knowledge about impulsivity which can significantly affect the quality of life of patients and their relatives is limited. In this study, we aimed to determine whether there is a relationship between MS and impulsivity.Material and Methods: MS patients and healthy controls were included in this paired case-control study. The clinical (disability rate, duration of disease, clinical course) of MS patients and demographics (age, gender, income status, marital status, educational status) characteristics of the whole population were questioned. Beck depression scale and Barrat's impulsivity scale were applied to all participants. The patient and control groups were compared in terms of impulsivity. Considering that depression is frequently observed in MS patients and depression may affect impulsivity, the groups were compared again with covariance analysis.Results: The study included 60 MS patients of whom 41 was female and 51 healthy controls of whom 40 was female. Cognitive impulsivity was significantly higher in the MS group, and the MS group was significantly depressive than the controls. This difference in cognitive impulsivity continued after the effect of depression stabilized.Conclusion: Impulsivity was significantly higher in MS patients than in normal controls. Approaches that take into account impulsivity may be useful in the treatment of MS.
Keywords: Multiple sclerosis; impulsivity; neuropsychiatric symptom